The hope of winter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
It has long been common in the dry winter season in rural Malawi to see a person in somewhat shabby gear going down to the riverside with a watering can in hand. Not that this picture of smallholders working in their fruit, vegetable and legume...